Perencanaan Perkerasan Kaku pada Ruas Jalan Simpang 3 Pengabuan – Pengabuan Timur dengan Metode MDP Tahun 2024 - Kartika, Tiara; Saloma, Saloma; Putra Usman, Arie (UNIVERSITAS SERAMBI MEKKAH, 2025)
Roads are one of the factors to strengthen the economic facilities and infrastructure of the people based on resources and help the region in the openness of isolated villages and sub-districts in Penukal Abab Lematang Ilir Regency (PALI), the Simpang 3 Pengabuan - Pengabuan Timur Road Section is one of the road sections that connects the provincial road Lembak - Modong Road Section and is a priority area for plantations. This section is one of the priority roads in the region, so planning is needed on the Simpang 3 Pengabuan - Pengabuan Timur road section using the 2024 Pavement Design Manual. The planned age of the Simpang 3 Pengabuan - Pengabuan Timur road section is 20 years with a CBR value of 7.54% JSKN plan of 80369.36466 units with a road length of 2.524 km. The results obtained were the design of concrete with a low traffic category with a concrete slab thickness of 200 mm, a thin concrete thickness of 100 mm, an aggregate foundation layer with a thickness of 150 mm and having a Tie Bar with a transverse joint distance of 4 m.